Der Weg zur Theologie-Professur ist hart – gerade für Religionslehrer! - Caruso, Carina (katholisch.de, Kolumne „Mein Religionsunterricht“.)

Inszenierungen im digitalen Bild. Eine Rekonstruktion der Selfie-Praktiken Jugendlicher mittels der Dokumentarischen Bildinterpretation. - Schwabl, Franziska

Fotografien als Zugang zur Lebenswelt Jugendlicher. Eine Analyse der digitalen Inszenierungspraktiken Jugendlicher im berufsschulischen Übergangssystem. - Schwabl, Franziska (bwp@Berufs-und Wirtschaftspädagogik – online)

Optimierung von Organisationsstrukturen für die emotionale und soziale Entwicklung? Wissenschaftliche Begleitung des Projekts „Geschwisterklassen“ - online. - Scheer, D.; Laubenstein, Désirée

Auswirkungen der Corona-Schulschließungen auf Schülerinnen und Schüler mit und ohne Förderbedarf der emotionalen und sozialen Entwicklung (COFESE) - online. - Scheer, D.; Laubenstein, Désirée

Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Schlangenotto, Darius; Schnedler, Wendelin; Vadovic, Radovan (Games)

Revisiting a Remedy Against Chains of Unkindness - Schnedler, Wendelin; Stephan, Nina Lucia (Schmalenbach Business Review)

Werberecht (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) 2. Auflage - Krimphove, Dieter

Reverse Factoring: Eine alternative Finanzierungsform in der Praxis - Krimphove, Dieter; Lüke, Christoph (Corporate Finance)

Nachhaltigkeit und Compliance - Krimphove, Dieter (Compliance Berater)

EuGH entscheidet zu Lücken im Europäischen Vorrangsprinzip - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Designing a Geometry Capstone Course for Student Teachers: Bridging the gap between academic mathematics and school mathematics in the case of congruence - Hoffmann, Max; Biehler, Rolf (INDRUM 2020, Université de Carthage, Université de Montpellier, Sep 2020, Cyberspace (virtually from Bizerte), Tunisia)
At Paderborn University, a new 6th semester geometry-course for upper secondary student teachers has been designed and taught by the first author of this paper. To show links between academic mathematics and school mathematics we established so-called interface weeks. These are weeks during a course in which lecture, exercises and homework focus on topics that are related to the normal canon of content but specially chosen for their relevance in school contexts. In this article, we want to present our design for an interface week on the topic of congruence. In order to do so, we first illustrate how so-called interface aspects are used to systematize the mathematical background of the topic, thus giving future mathematics teachers the chance to act professionally. We then show examples of learning activities and first results of the accompanying research.

Antike und mittelalterliche Grundlagen frühneuzeitlicher Friedensvorstellungen - Kamp, Hermann (Handbuch Frieden im Europa der Frühen Neuzeit / Handbook of Peace in Early Modern Europe)

Culture of Politics in the Middle Ages: Rituals to create and confirm political order - Kamp, Hermann (The Routledge Companion to Cultural History in the Western World)

Einleitung - Kamp, Hermann; Schmitz, Sabine (Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung)

Vom Franzosenfeind zum Fußballfreund. Jan Breydel im Gedächtnis der Belgier, Flamen und Brügger Bürger - Kamp, Hermann (Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung)

Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung

Extending Loyalty Programs with BI Functionalities A Case Study for Brick-and-Mortar Stores - Kucklick, Jan-Peter; Kamm, Michael Reiner; Schneider, Johannes; vom Brocke, Jan (Proceedings of the 53rd Hawaii International Conference on System Sciences)
Effective customer loyalty programs are essential for every company. Small and medium sized brick-and- mortar stores, such as bakeries, butcher and flower shops, often share a common overarching loyalty program, organized by a third-party provider. Furthermore, these small shops have limited resources and often cannot afford complex BI tools. Out of these reasons we investigated how traditional brick-and- mortar stores can benefit from an expansion of service functionalities of a loyalty card provider. To answer this question, we cooperated with a cross-industry customer loyalty program in a polycentric region. The loyalty program was transformed from simple card-based solution to a mobile app for customers and a web- application for shop owners. The new solution offers additional BI services for performing data analytics and strengthening the position of brick-and-mortar stores. Participating shops can work together in order to increase sales and align marketing campaigns. Therefore, shopping data from 12 years, 55 shops, and 19,000 customers was analyzed.
Keywords: brick-and-mortar stores; business intelligence; case study; loyalty program

Human-Machine Learning und Digital Commons. K/Ein Manifest - Weber, Jutta (Das Argument)

Data mining for small shops: Empowering brick-and-mortar stores through BI functionalities of a loyalty program1 - Kamm, Michael Reiner; Kucklick, Jan-Peter; Schneider, Johannes; vom Brocke, Jan (Information Systems Management)
While the analysis and usage of data are increasing in importance, the application of sophisticated BI solutions in small stores is limited by available technical capabilities and financial resources. This study investigates how brick-and-mortar stores can benefit from an expansion of service functionalities of a cross-industry loyalty card provider. Digitalizing the loyalty program created new opportunities, while the analysis of shopping data of 13 years, 19,000 customers, and 55 shops empowered data-based decision support.
Keywords: Customer loyalty; case study; brick-and-mortar stores; business intelligence; loyalty programs